Criteria-Based Rehabilitation Following Revision Hip Arthroscopy: A Clinical Commentary - Haley Leo; Trevor Shelton; Helen Bradley (North American Sports Medicine Institute, 2023)
Hip revision arthroscopy is becoming an increasingly popular surgery for those with unsatisfactory outcomes following primary hip arthroscopy. With the relatively uncommon but potentially increased difficulty of rehabilitation from this surgery, a lack of established research regarding rehabilitative programs remains. Therefore, the purpose of this clinical commentary is to propose a criterion-based progression that considers the intricacies present following a hip revision arthroscopy from early rehabilitation through return to sport. Criteria are presented clearly to promote objective progression through rehabilitation as opposed to relying on time since surgery as revision surgeries do not always follow traditional tissue healing time-frames. This criterion based progression promotes range of motion (ROM), strength, gait, neuromuscular control, load introduction and gradual return to play. # Level of Evidence 5